On ἐλευθερία, τὸ ζῆν ὡς βούλεταί τις, and Virtue in the Aristotelian Theory of Demokratia - Wolf, Eduardo (Revista Archai, 2024)
In this paper, I aim to reject the thesis that ancient democracy, according to Aristotle, is defined by majority rule for its own benefit. I advocate for an alternative thesis, (which easily incorporates what is true in the rejected view), namely, that it is the concept of eleutheria, particularly as understood in Politics VI.2 and VI.9, that holds what I call "definitional prominence" relative to the concept of demokratia.